Analisis Pengaruh Ukuran Perusahaan, Profitabilitas, Solvabilitas, dan Ukuran KAP terhadap Audit Report Lag pada Perusahaan Food and Beverage yang Terdaftar di BEI : Periode 2021-2024 - Ainun Jariyah; M. Muhayin A Sidik; Dewi Zakia (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study examines the influence of firm size, profitability, solvency, and public accounting firm (KAP) size on audit report lag among food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research employs purposive sampling, involving 68 companies with a total of 272 observations, and uses multiple linear regression analysis after passing all classical assumption tests. The findings reveal that profitability measured by Return on Equity (ROE), solvency measured by Debt to Assets Ratio (DAR), and KAP size have a significant effect on audit report lag. Meanwhile, firm size (measured by total assets and total sales), profitability measured by Return on Assets (ROA), and solvency measured by Debt to Equity Ratio (DER) show no significant effect. These results indicate that companies with higher ROE, greater DAR, and those audited by Big Four accounting firms tend to complete their audit process more promptly. The study highlights that both financial performance and auditor characteristics play essential roles in determining audit timeliness. Overall, this research provides valuable insights for management, auditors, investors, and regulators to enhance the efficiency and reliability of financial reporting.